Morphometry of Daphnia lumholtzi in Lake Texoma, OK, USA - Jessica E Beyer; K David Hambright (PANGAEA, 2019)
In Lake Texoma, OK, USA, we measured the morphometry of Daphnia lumholtzi. Samples were collected at five pelagic sites (see below for coordinates) over the course of fourteen months (June 2010-July 2011). Zooplankton were collected using vertical tow over the full water column (depth-integrated) with a Wisconsin-type net (350-μm mesh, aperture diameter 10.5 cm). Zooplankton were enumerated and morphology of Daphnia lumholtzi was measured using a dissecting microscope.
In supplement to: Beyer, JE; Hambright, KD (2019): The niche and morphology of the invasive Daphnia lumholtzi in a subtropical reservoir, 20 years after invasion. Journal of Plankton Research, 41(2), 90-100, https://doi.org/10.1093/plankt/fby053